Residents’ satisfaction on property management service in public rental housing: a study of Chongqing, China - Tang, Haoling (2022)
Based on the theory of property service quality and customer satisfaction theory, focusing on the actual problems between the insured public housing and property management services, this paper uses the SERVQUAL model based on the actual situation of Chongqing where public housing is located, and establishes 37 indicator through the service quality model, and selects the three earliest public housing communities in Chongqing as the research object to implement the research, from the overall level The research was conducted from the overall level to the subdivision of 5 dimensions to investigate the satisfaction and discuss and analyses the problems in the public housing property services. Based on the identified problems into indepth analysis, this paper concludes with constructive suggestions for improvement. Firstly, to strengthen the ability to fulfil the service commitment to the public and provide reliable guidance services, property companies need to invest more human and material resources in this a rea and should adopt a series of systems and supporting measures to continue to maintain highquality service content and meet the needs of tenants. Secondly, property companies should pay more attention to the complaints arising from tenants' enjoyment of property services, to facilitate realtime monitoring of problems in property management services and solve them at any time, which will play an important role in improving the quality of property services. Finally, the property management company should pay more attention to the individual needs of the tenants, try to understand the general requirements of the tenants, and start from the best interests of the tenants. At the same time, the property management team understands the special needs of the resi individual needs of the residents mentioned earlier.